2004
DOI: 10.5713/ajas.2004.594
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inbreeding on Lamb Survival in a Flock of Muzaffarnagari Sheep

Abstract: A pedigree file of 4,628 records of Muzaffarnagari sheep, maintained at Central Institute for Research on Goats (CIRG), Makhdoom, was used to calculate the inbreeding coefficient of the flock. The flock had been closed for about 25 years (1978 to 2002). The investigation was aimed to study the effects of inbreeding on survivability of lambs. The cumulative survivability of lambs i.e., lambs survived up to 3, 7 and 15 days, 1, 2, 3, 6, 9 and 12 months after birth was considered for the study. The average level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 11 publications
3
14
1
Order By: Relevance
“…27). As in studies of other mammals (11,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), we found that HO and IR were highly correlated, and results were similar for the two heterozygosity estimates, with IR exhibiting the higher correlation with fitness. In both males and females, individuals with more heterozygous microsatellite loci had the highest reproductive success, as measured by the number of offspring produced.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…27). As in studies of other mammals (11,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), we found that HO and IR were highly correlated, and results were similar for the two heterozygosity estimates, with IR exhibiting the higher correlation with fitness. In both males and females, individuals with more heterozygous microsatellite loci had the highest reproductive success, as measured by the number of offspring produced.…”
Section: Discussionsupporting
confidence: 66%
“…A growing number of studies have shown that these estimators of genetic diversity are correlated with a range of fitness components, including survival, disease susceptibility, and reproductive success (11,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The general consensus of these studies is that an association exists between multilocus heterozygosity and components of fitness (26).…”
mentioning
confidence: 99%
“…1998; Gharrett et al . 1999; Mandal et al . 2004), and to negatively affect both growth (Coltman et al .…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of increased homozygosity at loci affecting fitness are often negative, either because recessive deleterious alleles are expressed or because homozygosity reduces heterozygote advantage [Charlesworth & Charlesworth, 1987]. The strong detrimental effects of inbreeding in animal populations can include reduced overall fertility [Amos et al, 2001;Charpentier et al, 2005a;Gallardo et al, 2004;Hoffman et al, 2004;Seddon et al, 2004;Slate et al, 2000], affected growth [Charpentier et al, 2006;Coltman et al, 1998;Pujolar et al, 2005], reduced survival [Coulson et al, 1998[Coulson et al, , 1999Mandal et al, 2004], and increased disease susceptibility [Acevedo-Whitehouse et al, 2003]. Inbreeding depression thus appears to have the potential to shape life history, behavioral, morphological and physiological traits in all living species, from simple to complex.…”
Section: Introductionmentioning
confidence: 99%